PMM.46 Investigating Hypoglycaemia in Type 1 diabetes during pregnancy. (9th June 2014) - Vermont, L; Hussain, S; Lam, S; Jarvis, S; Cheng, F; Jairam, C; Jones, B; Dornhorst, A
Abstract : Aims: In pregnant type 1 diabetes patients the incidence of severe hypoglycaemia increases by 6-fold. This prospective observational study assesses the prevalence of impaired awareness of hypoglycaemia (IAH) and frequency of hypoglycaemia in pregnant type 1 diabetes patients. Methods: Impaired awareness of hypoglycaemia (IAH) was assessed using three validated questionnaires (Clarke, Gold and Pederson). These questionnaires were amalgamated into a single questionnaire which also incorporated the Edinburgh Hypoglycaemic Score, questions on causes and worry for hypoglycaemia scored on a 7-point Likert scale. Questionnaires, self-monitored blood glucose diaries and Diasend® metre downloads were collected from the pregnant patients on a fortnightly basis. Results: 8 pregnant and 22 matched non-pregnant female type 1 diabetic patients were recruited. In keeping with previous observations, there was increased prevalence of IAH in pregnant patients compared to non-pregnant subjects. There was no significant difference in severe hypoglycaemia or proportion of blood glucose readings below 3.5 mmol/L during pregnancy between IAH and aware patients. Pregnant subjects were significantly more worried about nocturnal hypoglycaemia than daytime hypoglycaemia (p = 0.007). Patients with IAH felt more worried about hypoglycaemia compared to aware patients (p = 0.04). Comparison of blood glucose diaries and metre downloads highlighted underreporting of hypoglycaemic events on diaries. Conclusions: This report demonstrates increased prevalence of IAH during pregnancy. Further research is required to fully assess whether IAH assessed via questionnaires in clinic can predict higher incidence of hypoglycaemia or severe hypoglycaemia in patients. The findings of this study highlights potential for improved detection of hypoglycaemic episodes using technology.